TAHAP PERKEMBANGAN AFEKTIF ANAK USIA DINI : TAHAP PERKEMBANGAN AFEKTIF ANAK USIA DINI - Radithiya Nur Rahman Pakudu; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2022)
Early childhood affective development is linked to children's emotional and social growth, which includes their capacity to recognize, communicate, and regulate their emotions as well as form social connections with others. Early infancy emotional development phases include: Stage 1: Infant (0–12 months) Children at this age start to identify their own sentiments as well as other people's feelings through body language and facial expressions. Children start to learn how to control their emotions and express them by crying or smiling. 2. Toddler (1-3 years) Stage This stage marks the beginning of the child's ability to recognize and verbalize his feelings. Children also start to learn how to cultivate empathy and comprehend the.